Neuroserpin Differentiates Between Forms of Tissue Type Plasminogen Activator via pH Dependent Deacylation - Carlson, Karen-Sue B.; Nguyen, Lan; Schwartz, Kat; Lawrence, Daniel A.; Schwartz, Bradford S. (Frontiers in Cellular Neuroscience, 2016)
Tissue-type Plasminogen Activator (t-PA), initially characterized for its critical role in fibrinolysis, also has key functions in both physiologic and pathologic processes in the CNS. Neuroserpin (NSP) is a t-PA specific serine protease inhibitor (serpin) found almost exclusively in the CNS that regulates t-PA’s proteolytic activity and protects against t-PA mediated seizure propagation and blood-brain barrier disruption. This report demonstrates that NSP inhibition of t-PA varies profoundly as a function of pH within the biologically relevant pH range for the CNS, and reflects the stability, rather than the formation of NSP: t-PA acyl-enzyme complexes. Moreover, NSP differentiates between the zymogen-like single chain form (single chain t-PA , sct-PA) and the mature protease form (two chain t-PA, tct-PA) of t-PA, demonstrating different pH profiles for protease inhibition, different pH ranges over which catalytic deacylation occurs, and different pH dependent profiles of deacylation rates for each form of t-PA. NSP’s pH dependent inhibition of t-PA is not accounted for by differential acylation, and is specific for the NSP-t-PA serpin-protease pair. These results demonstrate a novel mechanism for the differential regulation of the two forms of t-PA in the CNS, and suggest a potential specific regulatory role for CNS pH in controlling t-PA proteolytic activity.